High isoniazid resistance rates in rifampicin susceptible Mycobacterium tuberculosis pulmonary isolates from Pakistan. - Naima Fasih (Public Library of Science (PLoS), 2012)
Background Rapid new diagnostic methods (including Xpert MTB/RIF assay) use rifampicin resistance as a surrogate marker for multidrug resistant tuberculosis. Patients infected with rifampicin susceptible strains are prescribed first line anti-tuberculosis therapy. The roll out of such methods raises a concern that strains with resistance to other first line anti-tuberculosis drugs including isoniazid will be missed and inappropriate treatment given. To evaluate implications of using such methods review of resistance data from high burden settings such as ours is essential. Objective To determine resistance to first line anti-tuberculosis drugs amongst rifampicin susceptible pulmonary Mycobacterium tuberculosis (MTB) isolates from Pakistan. Materials and methods Data of pulmonary Mycobacterium tuberculosis strains isolated in Aga Khan University Hospital (AKUH) laboratory (2009-2011) was retrospectively analyzed. Antimicrobial susceptibility profile of rifampicin susceptible isolates was evaluated for resistance to isoniazid, pyrazinamide, ethambutol, and streptomycin. Results Pulmonary specimens submitted to AKUH from 2009 to 2011 yielded 7738 strains of Mycobacterium tuberculosis. These included 54% (n 4183) rifampicin susceptible and 46% (n: 3555) rifampicin resistant strains. Analysis of rifampicin susceptible strains showed resistance to at least one of the first line drugs in 27% (n:1133) of isolates. Overall isoniazid resistance was 15.5% (n: 649), with an isoniazid mono-resistance rate of 4% (n: 174). Combined resistance to isoniazid, pyrazinamide, and ethambutol was noted in 1% (n: 40), while resistance to isoniazid, pyrazinamide, ethambutol, and streptomycin was observed in 1.7% (n: 70) of strains. Conclusions Our data suggests that techniques (including Xpert MTB/RIF assay) relying on rifampicin susceptibility as an indicator for initiating first line therapy will not detect patients infected with MTB strains resistant to other first line drugs (including isoniazid). The roll out of these techniques must therefore be accompanied by strict monitoring ensuring early resistance detection to increase chances of improved patient outcomes.